Total quality management in higher education case study in Marmara University Engineering Faculty - Külahçı, A. Ersel (My University, 1995)
unknown
Keywords: TOPLAM KALİTE YÖNETİMİ,EĞİTİMDE; ÜNİVERSİTELER-KALİTE YÖNETİMİ